The Denominations of the Currency in Relation to the Gold Problem - Lockhart, Oliver Cary (Quarterly Journal of Economics, 1924)
The possibilities of a credit expansion based on the vast stock of gold in Federal Reserve banks, 234. — Federal Reserve notes in denominations of $10 and $20 displaced gold certificates of the same denominations, 239. — Statistics on reserve notes, gold certificates, money in circulation, 240. — Proposed withdrawal of $10 and $20 reserve notes and substitution of gold certificates, 244. — Advantages of the plan, 247.